2019
DOI: 10.1007/s11113-019-09516-3
|View full text |Cite
|
Sign up to set email alerts
|

The Gap Between Lifetime Fertility Intentions and Completed Fertility in Europe and the United States: A Cohort Approach

Abstract: We study the aggregate gap between intended and actual fertility in 19 European countries and the US based on a cohort approach. This complements prior research that had mainly used a period approach. We compare the mean intended number of children among young women aged 20 to 24 (born in the early 1970s), measured during the 1990s in the Fertility and Family Surveys, with data on completed fertility in the same cohorts around age 40. In a similar manner, we compare the share who state that they do not want a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 60 publications
(78 reference statements)
3
75
0
1
Order By: Relevance
“…Thus, the gap between desired and actual fertility varies substantially across Europe (Bongaarts 2001;Goldstein et al 2003). Consistent with previous work (Bongaarts, 2001;Quesnel-Valleé and Morgan 2003), both Testa (2012) and Beaujouan and Berghammer (2017) find that, across educational groups, the shortfall in births is larger on average among highly-educated women in Europe.…”
Section: Selection and Convergence?supporting
confidence: 82%
See 1 more Smart Citation
“…Thus, the gap between desired and actual fertility varies substantially across Europe (Bongaarts 2001;Goldstein et al 2003). Consistent with previous work (Bongaarts, 2001;Quesnel-Valleé and Morgan 2003), both Testa (2012) and Beaujouan and Berghammer (2017) find that, across educational groups, the shortfall in births is larger on average among highly-educated women in Europe.…”
Section: Selection and Convergence?supporting
confidence: 82%
“…Fertility was lowest among the mosteducated women, many of whom chose to devote more resources to each child rather than more time to childbearing, and thus reduced their family size. However, because fertility intentions among the most-educated remained relatively high, the gap between their intended and actual fertility became relatively wide in most countries (Testa 2014;Beaujouan and Berghammer 2017). Interestingly, new evidence, particularly since the recent Great Recession, suggests that there has been a gradual convergence in fertility rates among educational groups and a flattening of the existing negative educational-fertility gradient in some countries, such as the United States (Pew Research 2013 for the U.S.).…”
Section: Introductionmentioning
confidence: 99%
“…The convergence hypothesis follows the literature showing that, in high-income societies, differentials become smaller in absolute and relative terms. Jalovaara et al (2018) found that among the highly educated societies of Denmark, Norway and Sweden, there are almost to no differentials in the ultimate fertility of women between education categories 10 (see also Beaujouan & Berghammer, 2019).…”
Section: Population Projections By Levels Of Educationmentioning
confidence: 99%
“…Many couples postpone first birth to ever later ages, which in turn depresses period fertility rates (Bongaarts 2002). Low-fertility countries also display a persistent gap between desired family size, which is often at or around two children, and considerably lower levels of actual fertility (Beaujouan and Berghammer 2019), indicating that many women and couples are not able to realise their fertility aspirations.…”
Section: Demographic Perspectives On Fertility Transitionmentioning
confidence: 99%
“…For instance, the SDG pace scenario for Japan envisions a TFR of 1.20 in 2100, with a CI_95 ranging from 0.95 to 1.85. decades as compared with the other scenarios ( Figure 6 above). Considering unrealised desire for more children among many couples (Beaujouan and Berghammer 2019) and the trend to higher gender equality and more generous family policies, a more deeply thought-through scenarios broadly compatible with SDGs could instead imply a modest fertility recovery due to higher levels of gender equality and more extensive government support for families.…”
Section: Main Issues With the Ihme/gbd Fertility Scenariosmentioning
confidence: 99%